Circ_0004018 suppresses cell proliferation and migration in hepatocellular carcinoma via miR-1197/PTEN/PI3K/AKT signaling pathway. Issue 20 (18th October 2021) - Wang, He; Zhang, Qiao; Cui, Wenyu; Li, Wenlan; Zhang, Jimei
ABSTRACT: Hepatocellular carcinoma (HCC) is a common type of primary liver cancer. Circular RNAs (circRNAs) have been demonstrated to be a crucial player in multiple cancers. However, a large number of circRNAs remain to be explored. Our study focused on investigating hsa_circ_0004018 in HCC. Firstly, we conducted quantitative reverse transcription PCR (RT-qPCR) to find that circ_0004018 was down-regulated in HCC cells. Western blot analysis was performed to detect the protein levels of phosphatase and tensin homologue (PTEN) and related factors of PI3K/AKT signaling pathway. From the results of functional assays, we found that overexpression of circ_0004018 significantly inhibited the proliferative and migratory capacities of HCC cells. The regulatory mechanism of circ_0004018 in HCC was determined by RNA immunoprecipitation (RIP), RNA pull-down, and luciferase reporter assays, thereby we knew that circ_0004018 regulated PTEN by sequestering microRNA-1197 (miR-1197) to modulate PI3K/AKT signaling pathway. Finally, rescue assays verified that circ_0004018 participated in modulation of cell proliferation and migration in HCC via sponging miR-1197 and regulating PTEN. In conclusion, circ_0004018 suppresses the proliferation and migration of HCC cells via sponging miR-1197 to inactivate the PTEN/PI3K/AKT signaling pathway. Abbreviations: HCC: Hepatocellular carcinoma; circRNAs: Circular RNAs; PTEN: Phosphatase and tensin homologue; miR-1197: microRNA-1197; ceRNA: competitive endogenous RNA; ATCC: American Type Culture Collection; EMEM: Eagle's Minimum Essential Medium; RT-qPCR: Quantitative real-time PCR; EdU: 5-ethynyl-20-deoxyuridine; FISH: Fluorescent in situ hybridization; RIP: RNA immunoprecipitation; 3ʹ-UTR: 3ʹ-untranslated region; Wt: wild-type; Mut; mutant type; gDNA: genomic DNA; Act D: Actinomycin D; PI3K: phosphatidylinositol-3-kinase; AKT: protein kinase; lncRNAs: long non-coding RNAs